2006
DOI: 10.1007/s11837-006-0229-z
|View full text |Cite
|
Sign up to set email alerts
|

Numerically modeling oxide entrainment in the filling of castings: The effect of the webber number

Abstract: In the casting of aluminum alloys and, in general, in the casting of fi lm-forming alloys, the entrainment of oxides into the bulk liquid severely reduces the strength of the cast part. To avoid this, the melt velocity must be kept below a certain value, namely critical velocity, which is widely assumed to be 0.5 m/s. In this paper the authors investigate, by means of fl uid-dynamic computer simulation, the dependence of critical velocity on geometrical features of the running channels and thermophysical prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The limiting velocity depends on material and geometry parameters and ensures a controlled filling and avoids air entrainment. For aluminum alloys, the critical velocity ranges from 0.3 m/s to 0.5 m/s for a channel thickness between 3 mm and 25 mm [17].…”
Section: Process Simulationmentioning
confidence: 99%
“…The limiting velocity depends on material and geometry parameters and ensures a controlled filling and avoids air entrainment. For aluminum alloys, the critical velocity ranges from 0.3 m/s to 0.5 m/s for a channel thickness between 3 mm and 25 mm [17].…”
Section: Process Simulationmentioning
confidence: 99%
“…However, filling velocity was not the only oxide entrainment criterion ever considered. Kuo et al proposed to consider the Reynolds number as an oxide entrainment criterion instead [4], while Cuesta et al proposed to consider the Weber number [5]. Indeed, analyzing fluid flow simulation of different alloys and channels geometries, they highlighted the additional influence of the channel geometry in the flow structure.…”
Section: Introductionmentioning
confidence: 99%
“…Cuesta et al have found that the amount of oxide entrained into the liquid is related to the We number[75]. Reilly et al have used the calculated Froude number entrainment criterion to assess the overall quality of the running system, and their predictive results correlated well against quantitative data (Weibul moduli) obtained by experiments assessing three different running systems[54].…”
mentioning
confidence: 99%